Paciente de sexo masculino de 5o años de edad con hipertensión arterial y obesidad mórbida. - Mosquera Briones, Jazmín Lissette (2020)
The heart is one of the most important organs of our body, it is the one that is responsible for the transport of oxygen-rich blood to all the cells of our body, when the blood flows through the arteries it does so through pressure exerted by the walls of the arteries called blood pressure; Obesity is one of the determining factors in the increase in blood pressure, because when a lot of bad LDL cholesterol circulates through the blood, it tends to accumulate in the arteries as it accumulates, reducing blood flow and our arteries will exercise greater pressure is going to make our heart, increasing the risk of vascular diseases; The following case refers to a 50-year-old masculine with a history of morbid obesity since adulthood, recently diagnosed with arterial hypertension with treatment of losartan 100 mg. Due to the patient's history and altered lipid profile as well as her blood pressure, the doctor refers her to the nutrition service for intervention. An individualized nutritional plan is carried out focused on both the socioeconomic, cultural and pathological level of the patient, a normocoloric diet is carried out, with hyposodic, hypo-fat, normocarbonate characteristics, high in fractionated fiber in 4 meal times, taking into account Note that you should increase the intake of fruits, vegetables, dairy products and their skimmed derivatives, increase the consumption of complex carbohydrates and reduce simple, polyunsaturated and monounsaturated fats, with the aim of improving the nutritional status of the patient and at the same time normalize your high blood pressure levels.